Markers for Prediction of Early Onset Neonatal Infection in Pregnancies with Prelabour Rupture of Membranes - Ademi Ibishi, Vlora (Faculty of Medicine, Ss. Cyril and Methodius University, Skopje, 2016)
Introduction: Prelabour rupture of membranes (PROM) is a common event in obstetrics and early onset neonatal infection (EONI) is a serious neonatal consequence that can happen related to PROM. Early prediction of EONI is a desirable clinical goal because late diagnosis with delayed treatment increases neonatal morbidity and mortality. Despite ongoing research efforts, identifying efficient predictive markers of EONI in pregnancies with PROM remains a critical challenge. An additional challenge in developing countries is the availability and reliability of tests and testing. Aims of the study: The primary aim of this study is to investigate and to determine the predictive value for early onset neonatal infection of maternal serum C- reactive protein and white blood cell count and amniotic fluid glucose concentration, in patients presenting with prelabour rupture of membranes. The secondary aim of the study is to determine associated demographic and socio-economic risk factors for prelabour rupture of membranes in pregnant women of Kosova, a population that has not been studied related to PROM and EONI. This includes the rate of neonatal infection in newborn infants with a maternal history of prelabour rupture of membranes, other associated risk factors for early onset neonatal infection in pregnancies complicated with PROM, most common maternal complications, mode of delivery, and the antenatal care practices in Kosova. Material and Methods: A cross-sectional design was used to analyse a population of 200 pregnant women presenting to the Obstetrics and Gynecology Tertiary Center in Kosova (during 2013-2015) with prelabour rupture of membranes who gave birth to a single newborns. A questionnaire and evaluation form was used to collect data prospectively at admission and thereafter. Demographic characteristics collected included, antenatal profile, probable risk factors, mode of delivery and maternal and neonatal outcome were recorded and analyzed. Maternal serum, amniotic fluid, and vaginal swab samples were taken at the admission from all the women enrolled in the study with the purpose of determining the CRP, WBC, Glucose and maternal colonization. Results: In this study, 13 % of the newborns had EONI. The CRP cutoff value of >6 mg/L predicted early onset neonatal infection with a sensitivity of 92.3 %, a specificity of 60.9%, a PPV of 26.1 % and an NPV of 66 %. The area under receiver operating characteristics (ROC) curve for the maternal serum CRP was 0.84 (95 % CI, 0.745-0.934). Analysis of maternal white blood cell count and amniotic fluid concentration showed specificity, sensitivity, PPV and NPV of 57.6 %, 68.3%, 21.4 %, 91.5 % and 57.6 %, 33.9%, 11.5%, 84.3 % respectively. Identified risk factors for PROM included parity, previous PROM, and maternal colonization. Identified risk factors for PROM with EONI included the interval from membrane rupture to delivery, maternal genital tract colonization, newborn‟s birth weight, and gestational age at birth. Conclusion: Maternal serum CRP is the most accurate marker for prediction of EONI in pregnancies complicated with PROM, with a predictability of 84 %. This test is available in Kosova and is recommended to be conducted routinely in every pregnant women presenting with PROM. Maternal plasma WBC and amniotic fluid glucose concentration had a poor predictive value in prediction of EONI and may be used only as an additional test in combination with CRP for prediction of EONI in pregnancies complicated with PROM. It is also important to know that PROM- delivery interval, maternal colonization and gestational age and gestational weight at birth are associated risk factors for development of EONI as these can be evaluated critically when planning management of pregnancies complicated with PROM.
Докторска дисертација одбранета во 2016 година на Медицинскиот факултет во Скопје, под менторство на проф. д–р Розалинда Исјановска.
Keywords: markers of infection, prelabour rupture of membranes, early onset neonatal infection, prediction of infection